Market protection policy of the European Union against imports from China - Skrzypczyńska, Joanna (Wydział Nauk Politycznych i Dziennikarstwa Uniwersytetu im. Adama Mickiewicza w Poznaniu, 2017)
The aim of this paper is to analyze the European Union’s trade policy with regard to China in the context of the changes related to the expiry of the transitional period of China’s membership of the WTO in December 2016. The expiry of this transitional period necessitates certain changes in anti-dumping proceedings of the European Union. In order to achieve the purpose of the paper it has been assumed that granting or denying market economy status to China is primarily a political decision which requires taking into account contradictory interests of the EU member states.

Celem artykułu jest analiza polityki handlowej Unii Europejskiej wobec Chin w kontekście zmian jakie są związane z wygaśnięciem okresu przejściowego członkostwa Chin w WTO, które nastąpiło w grudniu 2016 roku. Wygaśnięcie owego okresu przejściowego wymusza na Unii Europejskiej pewne zamiany zwłaszcza w postępowaniach antydumpingowych. Dla zrealizowania celu pracy przyjęto że przyznanie lub nie statusu gospodarki rynkowej Chinom jest przede wszystkim decyzją polityczną wymagającą uwzględniani sprzecznych interesów państw członkowskich UE.
Polityka ochrony rynku Unii Europejskiej wobec importu z Chin
Keywords: European Union; China; dumping; trade policy; Unia Europejska; Chiny; dumping; polityka handlowa